FUNCTIONS THAT ASCERTAIN THE TEACHER'S PERSPECTIVE TO CONTROVERSIAL STATES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The ability of the future teacher to control himself in conflict situations in the educational process, to eliminate disagreements and anticipate unexpected conflicts, effectively use the principles that determine the fair resolution of mutual relations leads to good results.